Endometriosis in Focus: Modern Therapeutic Approaches for Enhanced Patient Outcomes - Review - Piekarska, Magda; Wojtkiewicz, Anna; Kudas, Zuzanna; Szerej, Krzysztof; Górka, Mateusz; Stec, Weronika (Quality in Sport, 2024)
Endometriosis (EM) is a chronic condition affecting millions of women globally, characterized by the growth of endometrial-like tissue outside the uterus. This review highlights the latest advancements in understanding and treating endometriosis, focusing on new therapeutic strategies aimed at improving patient care. The article briefly discusses the pathogenesis of endometriosis and reviews traditional treatment methods, including hormonal therapies (progestins, GnRH agonists, and oral contraceptives) and surgical interventions. It then explores the limitations of these conventional therapies and delves into newer strategies targeting specific molecular pathways, offering more effective symptom relief with fewer side effects. Emerging treatments that modulate the immune response and reduce inflammation are also examined, along with innovative approaches to pain management, both pharmacological and non-pharmacological. The review further considers alternative and supportive therapies, such as dietary changes, gut microbiota interventions, and complementary treatments like acupuncture, which may improve the overall management of endometriosis. This review emphasizes the shift toward more personalized, holistic care in treating endometriosis, with a focus on emerging therapies like Aromatase Inhibitors, GnRH receptor antagonists, and hormone receptor modulators. These approaches represent a significant advancement in improving the quality of life for women with this condition.